Mongol invasion of Transoxiana 1219-1221 AD - Ansori, Fahmi Moh (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Mongol invasion of the Islamic world, especially parts of Transoxiana, was a serious threat to the Islamic world. This invasion was the first gateway for the Mongols to carry out subsequent invasions to other parts of the Islamic world, which resulted in the Islamic world getting worse and experiencing enormous destruction. This research uses the historical method. History as a science has a method for studying, analyzing, and reconstructing events in the past. This research is included in Library Research or literature assessment. The Mongol invasion of the Islamic world marked the end of the classical centuries and the beginning of the Middle Ages in Islamic history. The Mongol invasion could not be underestimated in the capacity of its military forces. One of the factors in the defeat of the Islamic world to the Mongol invasion, namely from the Mongol military power itself, and coupled with the internal weakness of Muslims, which began to experience divisions in terms of power. Other than that, the mentality of the Muslims themselves in war has begun to look weak and they have begun to suffer from the disease of fear of death. So that those who are not afraid and are not afraid of death can excel in mastering the battlefield, like the Mongols.Keywords: Invasion, Mongols, Transoxiana